Oxytocin Normalizes Approach–Avoidance Behavior in Women With Borderline Personality Disorder - Schneider, Isabella; Boll, Sabrina; Volman, Inge; Roelofs, Karin; Spohn, Angelika; Herpertz, Sabine C.; Bertsch, Katja (Frontiers in Psychiatry, 2020)
Background: Interpersonal deficits are a core symptom of borderline personality disorder (BPD), which could be related to increased social threat sensitivity and a tendency to approach rather than avoid interpersonal threats. The neuropeptide oxytocin has been shown to reduce threat sensitivity in patients with BPD and to modify approach-avoidance behavior in healthy volunteers. Methods: In a randomized, double-blind placebo-controlled between-subject design, 53 unmedicated women with BPD and 61 healthy women participated in an approach-avoidance task 75-min after intranasal substance administration (24 IU oxytocin or placebo). The task assesses automatic approach-avoidance tendencies in reaction to facial expressions of happiness and anger. Results: While healthy participants responded faster to happy than angry faces, the opposite response pattern, i.e., faster reactions to angry than happy faces, was found in patients with BPD. In the oxytocin condition, the so-called “congruency effect” (i.e., faster avoidance of facial anger and approach of facial happiness vice versa) was increased in both groups. Notably, patients with BPD exhibited a congruency effect towards angry faces in the oxytocin but not in the placebo condition. Conclusions: This is the second report of deficient fast, automatic avoidance responses in terms of approach behavior towards interpersonal threat cues in patients with BPD. Intranasally administered oxytocin was found to strengthen avoidance behavior to social threat cues and, thus, to normalize fast action tendencies in BPD. Together with the previously reported oxytocinergic reduction of social threat hypersensitivity, these results suggest beneficial effects of oxytocin on interpersonal dysfunctioning in BPD.